Effect of herd size on subclinical infection of swine in Vietnam with influenza A viruses. Issue 1 (December 2016) - Takemae, Nobuhiro; Shobugawa, Yugo; Nguyen, Phuong; Nguyen, Tung; Nguyen, Tien; To, Thanh; Thai, Phuong; Nguyen, Tho; Nguyen, Duy; Nguyen, Dung; Do, Hoa; Le, Thi; et al.
Abstract Background Influenza A viruses of swine (IAV-S) cause acute and subclinical respiratory disease. To increase our understanding of the etiology of the subclinical form and thus help prevent the persistence of IAV-S in pig populations, we conducted active virologic surveillance in Vietnam, the second-largest pig-producing country in Asia, from February 2010 to December 2013. Results From a total of 7034 nasal swabs collected from clinically healthy pigs at 250 farms and 10 slaughterhouses, we isolated 172 IAV-S from swine at the weaning and early-fattening stages. The isolation rate of IAV-S was significantly higher among pigs aged 3 weeks to 4.5 months than in older and younger animals. IAV-S were isolated from 16 large, corporate farms and 6 family-operated farms from among the 250 farms evaluated. Multivariate logistic regression analysis revealed that "having more than 1, 000 pigs" was the most influential risk factor for IAV-S positivity. Farms affected by reassortant IAV-S had significantly larger pig populations than did those where A(H1N1)pdm09 viruses were isolated, thus suggesting that large, corporate farms serve as sites of reassortment events. Conclusions We demonstrate the asymptomatic circulation of IAV-S in the Vietnamese pig population. Raising a large number of pigs on a farm has the strongest impact on the incidence of subclinical IAV-S infection. Given that only some of the corporate farms surveyed were IAV-S positive, further active monitoring is necessary to identify additional risk factors important in subclinical infection of pigs with IAV-S in Vietnam.